Parasite and host biomass and reproductive output in barnacle populations in the rocky intertidal zone. Issue 3 (10th October 2018) - Fong, Caitlin R.; Kuris, Armand M.; Hechinger, Ryan F.
Abstract: The rocky intertidal zone has a long history of ecological study with barnacles frequently serving as a model system to explore foundational theories. Parasites are often ignored in community ecology studies, and this particularly holds for true for the rocky intertidal zone. We explore the role of the isopod parasite, Hemioniscus balani, on its host, the acorn barnacle, Chthamalus fissus. We use the currencies of biomass and reproduction measured at the individual level, then applied to the population level, to evaluate the importance of this parasite to barnacle populations. We found H. balani can comprise substantial biomass in 'apparent' barnacle populations, sometimes even equaling barnacle biomass. Additionally, parasite reproduction sometimes matched barnacle reproduction. Thus, parasites divert substantial energy flow from the barnacle population and to near-shore communities in the form of parasite larvae. Parasites appeared to decrease barnacle reproduction per area. Potentially, this parasite may control barnacle populations, depending on the extent to which heavily infected barnacle populations contribute to barnacle populations at larger scales. These findings regarding the importance of a particular parasite for host population dynamics in this well studied ecosystem call for the integration of disease dynamics into community ecological studies of the rocky intertidal zone.